Բարբառային նիւթերը «Արարատ» հանդէսի էջերում - Մեսրոպեան, Հայկանուշ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены диалектные тексты и публикации, связанные с теорией диалектологии, нашедшие место на страницах «Арарат». Вышедшие в свет в научно-духовном журнале материалы отобраны, классифицированы и представлены в трех основных группах: а) православные проповеди, религиозно-церковные и другие статьи в которых нашли место диалектные грамматические формы, слова, словосочетания и выражения, б) чисто диалектные тексты и фрагменты, вошедшие в исследования, написанные на литературном армянском языке, в) исследования по диалектологии, статьи, освещающие теоретические вопросы. Исследование показывает, что журнал «Арарат» предоставляет огромный материал для изучения армянских диалектов. И как пишут авторы редакционной статьи журнала, «Арарат» сыграл известную роль в развитии армянской филологии и церковной литературы. This article presents dialectal texts, publications related to the theory of dialectology, as well as publications of interest to Armenian dialectology, which found a place in the pages of “Ararat” journal. We have highlighted and classified the publications that were published in different issues of the spiritual-scientific journal. We have presented the various dialectal materials that exist in three main groups: a) orthodox sermons, religious-ecclesiastical and other articles that use dialectal grammatical forms, words, phrases and expressions, b) purely dialectal texts or extensive dialectal passages in studies written in literal Armenian language, c) dialectological studies, articles that highlight theoretical issues. The study shows that “Ararat” journal summarizes a huge dialectal material, which could become a separate important topic for the study of the Armenian dialects, as well as open a new path for the development of the Armenian modern dialectology. And as the authors of the editorial in the bibliography of this journal write, “Ararat” has played a prominent role in the development of Armenian philology and ecclesiastical literature. This journal can be included in the preferred list of important periodicals of Armenian studies.
Keywords: Հաղորդումներ; Հայ պարբերական հրատարակություններ